A Comparative Study between Staplers and Suture (Silk 2-0) for Skin Closure in Cesarean Sections at Gandaki Medical College Teaching Hospital - Jahan, K; Shrestha, R; Adhikari, P; Tripathi, M; Neupane, C P; Gurung, R T; Mally, J (Journal of Gandaki Medical College-Nepal, 2018)
Background: Skin closure in the abdominal surgeries is an important factor that affects the prognosis of wound in terms of hospital stay as well as overall outcome of the surgery. Objectives: Cesarean section being the commonly performed operation, choice of suture material has the unexceptional role on it. This study has been performed with an objective to look for the merits and demerits of the skin closure by suture (Silk 2-0) and stapler. Methods: Prospective comparative study conducted among the patients admitted in a Maternity Ward of Gandaki Medical College Teaching Hospital for elective and emergency cesarean section. The comparison has been made in terms of time taken during the skin closure, presence or absence of soakage and wound dehiscence, day of suture removal and pain during the suture removal. Results: The average time taken for skin closure for suture group was found to be 5.46 min (±0.97) and the same for stapler group was found to be 1.22 min (±0.15) respectively. Similarly, the mean day of stitch removal in suture and staples were found to be 6.94 (±1.75) and 7.95 (±1.89) respectively. Surgical site infection (SSI) i.e. soakage was present in eight percent of those in suture group and 20% in stapler group. Wound dehiscence was present in two percent among the suture group and five percent among the stapler group. The severity of pain is more in stapler group than that of suture group during its removal. Conclusions: Our study concluded suture being superior to staplers for skin closure during cesarean section. Though time taken for the closure is less in the stapler group, other factors like wound complications, duration of hospital stay, pain during its removal favored for the suture to be used. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 1-4